EXPERIMENTAL TRANSPLANTATION OF THE CLAM MERETRIX CASTA (CHEMNITZ) IN THE MARINE FISH FARM - Durve, V S (Indian Journal of Fisheries, 2011)
Several hundred clams, Meretrix casta (Chemnitz) obtained from Athankaraiestuary (Long- 79Â°E, Lat. 9Â° ICN.) on 28th Ostobjr, 1964, were transplanted in thepond of the flsh farm of the Central Marine Fisheries Research Institute, MandapamCamp- During the period of study extending over six months, it was found that therewas an initial high rate of growth in the seed clams immjdiately on transplantation.However, this rate of growth declined first slowly and then rapidly after five months.Probable causes for this uneven growth are discussed